myFoldl :: (a -> b -> a) -> a -> [b] -> a
myFoldl f z xs = foldr step id xs z
where step x g a = g (f a x)
I am currently readi
The thing will be become obvious when to expand the expression of foldr step id xs z
:
As Adam Smith said in the comments:
foldr step id xs z = (foldr step id xs) z
Consider foldr step id xs
firstly
foldr step id xs
= x1 `step` (foldr step id xs1)
= x1 `step` (x2 `step` (foldr step id xs2))
...
= x1 `step` (x2 `step` ... (xn `step` (foldr step id []))...)
= x1 `step` (x2 `step` ... (xn `step` id)...)
where
xs = (x1:xs1)
xs1 = (x2:xs2), xs = (x1:x2:xs2)
....
xsn = (xn:[]), xs = (x1:x2...xsn) respectively
Now, apply above function with argument z, i.e.
(x1 `step` (x2 `step` ... (xn `step` id)...)) z
and let
g = (x2 `step` ... (xn `step` id)...)
gives
(x1 `step` g) z
i.e.
(step x1 g) z
and now apply the where part of foldl:
where step x g a = g (f a x)
gives
(step x1 g) z = step x1 g z = g (step z x1)
where
g (step z x1) = (x2 `step` (x3 step ... (xn `step` id)...) (step z x1)
let
g' = (x3 step ... (xn `step` id)...)
gives
(x2 `step` g') (step z x1)
= step x2 g' (step z x1)
= g' (step (step z x1) x2))
= (x3 step ... (xn `step` id)...) (step (step z x1) x2))
repeats the same steps, finally we have,
(xn `step` id) (step ....(step (step z x1) x2)....)
= step xn id (step ....(step (step z x1) x2)....)
= id (step (step ....(step (step z x1) x2)....) xn)
= (step (step ....(step (step z x1) x2)....) xn)
= foldl step z xs
and now, it is obvious that why use id function. finally, see why
foldl step z xs = (step (step ....(step (step z x1) x2)....) xn)
initial case:
foldl step z' [] = z'
recursive case:
foldl step z (x1:xs1)
= foldl step (step z x1) xs1
= foldl step (step (step z x1) x2) xs2
...
= foldl step (step (step ....(step (step z x1) x2)....) xn) []
= (step (step ....(step (step z x1) x2)....) xn)
where
z' = (step (step ....(step (step z x1) x2)....) xn) in initial case
Just same as above.